Sir Arthur Evans and Minoan Crete : Creating the Vision of Knossos - Marinatos, Nanno (I.B.Tauris, 2014)
Front Cover -- Title Page -- Copyright -- Dedication -- Contents -- List of Illustrations -- Foreword -- Preface -- Introduction -- 1. Tree and Pillar Cult -- 2. Mourning Kybele: Arthur Evans and James Frazer -- 3. The Whirligig of Time: The Narrative of the Palace of Minos -- 4. Monotheism -- 5. The Ring of Nestor -- 6. The Ring of Minos -- 7. The Final Years: Evans's Restorations and his Vision of Knossos -- 8. Sir Arthur Evans and Spyridon Marinatos -- 9. The Last Visit of Evans to Crete -- 10. Sunt Lacrimae Rerum: The War and the Death of Evans -- Appendix 1 Letters between Sir Arthur Evans and Spyridon Marinatos -- Appendix 2 Letters between Edith Eccles and Spyridon Marinatos -- Appendix 3 The Relationship of John Pendlebury and Spyridon Marinatos -- Appendix 4 Letter of Spyridon Marinatos to Humfry Payne -- Appendix 5 Letters of Priest Nikolaos Pollakes to Spyridon Marinatos and his wife Maria Evangelidou -- Notes -- Bibliography -- Back Cover